Conversation with 2017 American Academy of Religion Excellence in Teaching award winner Lynn Neal - Neal, Lynn S. (Teaching theology and religion, 2018)
This conversation between the 2017 American Academy of Religion Excellence in Teaching award winner Lynn Neal and the editors of Teaching Theology and Religion continues an occasional series of interviews that has previously featured Jonathan Z. Smith, Stephen Prothero, Mary Pierce Brosmer, Mary Elizabeth Mullino Moore, and the 2016 Teaching award winner Joanne Maguire Robinson. The exchange takes as its point of departure the AAR teaching statement that Professor Neal submitted. Topics discussed include introductory courses, active learning assignments, religious intolerance and privatization, student learning outcomes, different levels of student skills and preparation, augmenting assignments through the production of video interviews with scholars, and finding conversation partners for reflecting on teaching under the life balance stresses of the academy today.